Future challenges for manufacturing - Bennett, David (Journal of manufacturing technology management, 2014)
Purpose – This Editorial Viewpoint explores what changes are taking place in manufacturing technology management with the aim of identifying future challenges that should be represented in the scope of JMTM. Design/methodology/approach – The viewpoints use an analysis of relevant articles in JMTM, published since 2007, which have focused on future challenges for manufacturing. It also draws on two recent reports. Findings – While the analysis confirms the inclusion of some subjects already in the journal scope, there are elsewhere gaps that merit it being expanded. Research limitations/implications – Evidence for the findings is only from a limited number of articles identified in this journal together supplemented by other secondary sources. Practical implications – There are implications for practice concerning the future of manufacturing from the analysis and the sources used, especially the reports. Originality/value – Although it has limitations, the article is based on original bibliographic research.